Extracts From Hypericum hircinum subsp. majus Exert Antifungal Activity Against a Panel of Sensitive and Drug-Resistant Clinical Strains. - Tocci, Noemi; Perenzoni, Daniele; Iamonico, Duilio; Fava, Francesca; Weil, Tobias; Mattivi, Fulvio (Frontiers in Pharmacology, 2018)
During the last two decades incidences of fungal infections dramatically increased and the often accompanying failure of available antifungal therapies represents a substantial clinical problem. The urgent need for novel antimycotics called particular attention to the study of natural products. The genus Hypericum includes many species that are used in the traditional medicine to treat pathological states like inflammations and infections caused by fungi. However, despite the diffused use of Hypericum-based products the antifungal potential of the genus is still poorly investigated. In this study five Hypericum species autochthonous of Central and Eastern Europe were evaluated regarding their polyphenolic content, their toxicological safety and their antifungal potential against a broad panel of clinical fungal isolates. LC-MS analysis led to the identification and quantification of 52 compounds, revealing that Hypericum extracts are rich sources of flavonols, benzoates and cinnamates, and of flavan-3-ols. An in-depth screen of the biological activity of crude extracts clearly unveiled H. hircinum subsp. majus as a promising candidate species for the search of novel antifungals. H. hircinum is diffused in the Mediterranean basin from Spain to Turkey where it is traditionally used to prepare a herbal tea indicated for the treatment of respiratory tract disorders, several of which are caused by fungi. Noteworthy, the infusion of H. hircinum subsp. majus excreted broad antifungal activity against Penicillium, Aspergillus and non-albicans Candida isolates comprising strains both sensitive and resistant to fluconazole. Additionally, it showed no cytotoxicity on human cells and the chemical characterization of the H. hircinum subsp. majus infusion revealed high amounts of the metabolite hyperoside. These results scientifically support the traditional use of H. hircinum extracts for the treatment of respiratory tract infections and suggest the presence of exploitable antifungal principles for further investigations aimed at developing novel antifungal therapies.